+0

((m^-3)(n^2)^-4)/((m^2)(n^-3))^2

0
261
2

((m^-3)(n^2)^-4)/((m^2)(n^-3))^2

A quick question, how do you get (m^8/n^2) out of this? I have no idea what to approach where. It's a little infuriating.

Guest May 7, 2017
Sort:

#1
+1

Simplify the following:
(1)/(((n^2)/(m^3))^4 ((m^2)/(n^3))^2)

Multiply each exponent in m^2/n^3 by 2:
(1)/((n^2/m^3)^4 (m^(2×2))/((n^3)^2))

2×2 = 4:
(1)/((n^2/m^3)^4 m^4/(n^3)^2)

Multiply exponents. (n^3)^2 = n^(3×2):
(1)/((n^2/m^3)^4 m^4/n^(3×2))

3×2 = 6:
(1)/((n^2/m^3)^4 m^4/n^6)

(n^2/m^3)^(-4) = (m^3/n^2)^4:
((m^3/n^2)^4)/(m^4/n^6)

Multiply each exponent in m^3/n^2 by 4:
((m^(4×3))/((n^2)^4))/(m^4/n^6)

4×3 = 12:
(m^12/(n^2)^4)/(m^4/n^6)

Multiply exponents. (n^2)^4 = n^(2×4):
(m^12/n^(2×4))/(m^4/n^6)

2×4 = 8:
(m^12/n^8)/(m^4/n^6)

Multiply the numerator by the reciprocal of the denominator, (m^12/n^8)/(m^4/n^6) = m^12/n^8×n^6/m^4:
(m^12 n^6)/(n^8 m^4)

Combine powers. (m^12 n^6)/(n^8 m^4) = m^(12 - 4) n^(6 - 8):
m^12 - 4 n^6 - 8

12 - 4 = 8:
m^8 n^(6 - 8)

6 - 8 = -2:

Guest May 7, 2017
#2
+6335
+4

This might be a little bit easier to see :)

$$\large \frac{(m^{-3}n^2)^{-4}}{(m^2n^{-3})^2} \\~\\ =\frac{m^{12}n^{-8}}{m^4n^{-6}} \\~\\ =m^{12-4}n^{-8--6} \\~\\ =m^{8}n^{-2} \\~\\ =\frac{m^{8}}{n^{2}}$$

hectictar  May 7, 2017

15 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details